Reliability Assessment and Technical Diagnostics of the Bridge Structure across the Verkhnia Khortytsia River in Zaporizhzhia - Dankevych, N. O; Piatnytsia, M. V (Science and Transport Progress, 2021)
Purpose. The authors aim to assess the reliability and technical diagnostics of the bridge structure, as well as to develop the methods for eliminating defects and restoring the serviceability of damaged building structures, as most accidents occur due to unsatisfactory technical condition of structures and their significant wear due to expiration of the standard service life. Methodology. An important role in the study is played by the formation of knowledge and skills of using a modern engineering approach to the survey of building structures in order to restore their serviceability. Inspections of construction sites are carried out in accordance with the rules set by the relevant regulations. Defects and damages are described in inspection materials with the indication of the possible reasons of their occurrence and forecasting their further influence on reliability and durability of construction. Findings. The analysis of scientific research and normative documents reflecting a problem of the operation safety increase of buildings and structures and estimation of a technical condition of structures is carried out in work. Methods of assessment of reliability and technical diagnostics of bridge constructions are applied. The results of the inspection are substantiated and recommendations are developed to ensure the serviceability and increase the service life of damaged structures of the object of study. Originality. Based on the design and technological documentation, normative base, scientific research, the model of competent systematization of the construction inspection data is obtained. Attention is paid to the timely major, as well as current medium repairs to improve the technical condition of the bridge elements, and in some cases the entire structure. Practical value. Application of the survey methods – visual and instrumental – allowed formulating the conclusions and recommendations aimed at widespread implementation in practice of assessing the reliability and technical condition of structures.